Perancangan Sistem Informasi Geografis Rumah Sakit di Kota Depok Berbasis Web Menggunakan Metode Location Based Service - Aziz Abiyasin (Syntax Corporation Indonesia, 2023)
Technological advances in the health sector are growing so rapidly One of the advances in information technology penetrating hospitals such as the use of information technology to support health information management. The hospital's geographic information system is not yet available to the people in Depok city. Many people still find it difficult to know the location and services of hospitals in their area. The purpose of this author is to design a geographic information system for hospitals in Depok city to make it easier for the people of Depok city to know the location, facilities, polyclinic services and doctor's practice schedule. The process of developing a geographic information system of this hospital uses a waterfall model with an analysis and design system assisted using a Unifield Modelling Language (UML) Diagram model. The system is designed using PHP and MySql programming languages as databases. To determine the location point using the Location Based Service (LBS) method. From this design produces a web-based geographic information system for hospitals in Depok city that can be useful for the people of Depok city in accessing information related to polyclinics, doctor schedules and hospital facilities.